The Effect Of Experiential Marketing On Consumer Satisfaction At Coffee Shops 1815 Mahat Kasan Street Gatot Subroto Banjarmasin - Muhammad Saleh; Muhammad Alif; Yulianisa’Dana (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2025)
This research is motivated by the mushrooming growth of coffee shops in Banjarmasin at this time, in fact, in almost every corner of the city of Banjarmasin there are many coffee shops standing. Kopi 1815 Banjarmasin is always busy with visitors and has loyal customers, has indoor and outdoor venues as well as an indoor smoking room. This makes the author interested in knowing the effect of experiential marketing on consumer satisfaction at the coffee shop 1815 Jalan Mahat Kasan Gatot Subroto Banjarmasin. This type of research is field research with a quantitative approach. The data collection technique uses a questionnaire and the data analysis technique uses simple linear regression analysis. The results of this research show that there is a positive influence of the Experiential marketing variable on coffee consumer satisfaction at 1815 Jalan Mahat Kasan Gatot Subroto Banjarmasin. From the results of a simple linear regression test, the equation Y= a+ b X or consumer satisfaction= 11.232+ 0.249. The results of the Coefficient of Determination (R2) test were 57.9% of customer satisfaction at the 1815 Banjarmasin coffee shop influenced by the Experiential Marketing variable. Meanwhile, the remaining 42.1% is influenced by other variables such as Marketing Strategy, Consumer Loyalty, and other variables outside this research.